Consumption of Fermented Plant Foods Is Associated with Systematic Differences in the Human Gut Microbiome and Metabolome. (29th May 2020) - Litwin, Nicole; Taylor, Bryn; Lejzerowicz, Franck; Poirel, Marion; Shaffer, Justin; Jiang, Lingjing; Aksenov, Alexander; Humphery, Gregory; Martino, Cameron; Miller-Montgomery, Sandrine; Dorrestein, Pieter; Veiga, Patrick; et al.
Abstract: Objectives: Fermented foods have gained much attention due to their proposed gut health benefits from recent clinical trials. However, very few studies have explored the effects of fermented foods, especially of plant origin, on gut microbiota composition and functional capacity in large human cohorts. Thus, the objective of this study was to assess whether self-reported fermented plant food consumption is associated with compositional or functional microbiome changes in a subset of individuals in the American Gut Project (AGP) cohort. Methods: Using a multi-omics approach (e.g., 16S rRNA amplicon sequencing, metagenomic sequencing, and untargeted mass spectrometry), we analyzed stool samples from 6811 healthy individuals from the AGP including 115 individuals specifically recruited for their fermented plant food consumption for a targeted four-week longitudinal study. Results: We observed subtle, yet statistically significant differences between fermented plant food consumers and non-consumers in beta diversity as well as differential taxa between the two groups. We found that the metabolome of fermented plant food consumers was enriched with conjugated linoleic acid (CLA), a putatively health-promoting compound. Cross-omic analyses between metagenomic sequencing and mass spectrometry suggest that CLA may be driven by taxa associated with fermented plant food consumers. Conclusions: Collectively, we found modest, yet persistent signatures associated with fermented plant food consumption that appear present in multiple omic types, which motivates further investigation of how different types of fermented foods may impact the human gut microbiome and overall health. Funding Sources: Danone Nutricia Research.